Synthesis of an isomer of lycoplanine a via cascade cyclization to construct the spiro-N,O-acetal moiety - Gao, Weiwei; Wang, Xiaodong; Yao, Linbin; Tang, Bencan; Mu, Guohao; Shi, Tao; Wang, Zhen (2021)
An isomer of lycoplanine A with a 6/10/5/5 tetracyclic skeleton was synthesized using D–A reaction and cascasde reaction to respectively construct the [9.2.2] pentadecane skeleton and the challenging 1-oxa-6-azaspiro[4.4]nonane spirocenter. Morever, detailed DFT calculations were conducted to explain the selectivity in the D–A reaction. This study may provide sufficient experience for the total synthesis of lycoplanine A and other alkaloids with similar spiro-N,O-acetal cores.